Basiacuong Masyarakat Kualu Nenas Kabupaten Kampar Provinsi Riau (Fungsi Sosial dan Nilai-Nilai Budaya) - Nurmalina Nurmalina (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2016)
Tradition Basiacuong a local culture that has wisdom that needs to be maintained. Advances in technology and the inclusion of new elements in the life of our nation is the cause of the shift in the values of life. This is the reason for researchers to conduct research with the aim of describing the social function basiacuong and describe the cultural values of society basiacuong Kualu Nenas. Basiacuong derived from the word flattered flattering from one party to another party who is usually represented by ninik mamak from a tribe that conversation. Basiacuong means menyengaja deed. Inside basiacuong have cultural values and social functions that must be maintained. Qualitative research with this descriptive method to analyze the function of social and cultural values in society basiacuong Kualu by making the community Kualu Nenas Nenas as research informants. Engineering research using audio-visual recording devices, recording sheet, and guidelines for the interview. Data collected in the form of text analyzed according to the research objectives by triangulation as a validation technique data. Based on the results it can be concluded that the social function of which is the tradition Basiacuong; (1) as a means of entertainment, (2) a means of education, (3) as a tool to maintain and pass customs, traditions, and culture (4) as a tool to show the identity of the person Kampar, and (5) can foster a cooperative spirit. In practice, the speech delivered in the tradition basiacuong contains many lessons or advice that is very educational for the audience, especially people Kualu Nenas.